(untitled) (Journal of Asian Development Studies, 2025)
For sustainability, South Asian economies are transitioning to renewable energy (RE) sources and modern technology and applying strict regulations. However, whether they compromise on productivity for environmental sustainability was unclear. To answer this question, this study aimed to empirically analyze the influence of RE transition, modernization, and regulations on the agriculture and industrial productivity of South Asian nations between 2000 and 2023. Before estimating the coefficients of the study, necessary pre-estimation diagnostic tests were performed to check econometric problems in the data. Thus, the study conducted the correlation matrix for multicollinearity, Pesaran cross-sectional dependency(CD) test for CD, Levin-Lin-Chu (LLC), Im-Pesaran-Shin (IPS), Fisher-ADF, and Fisher-PP tests for unit root, and Durbin-Watson test for autocorrelation. The study checked cointegration among variables through the Pedroni and Kao cointegration tests. Based on the results of these pre-estimation tests, the study employed the Fully Modified Ordinary Least Square (FMOLS) method to estimate the variables’ coefficients. The empirical outcomes revealed that the increase in RE transition and modernization significantly improved agricultural and industrial productivity. While regulations reduce the productivity of both the agricultural and industrial sectors. In the last, the study conducted the Dumitrescue-Hurlin test to check the direction of causality among the variables. The result indicates that agriculture and industrial productivity have a bidirectional causal relation with the RE transition, modernization, and regulations. However, the study finds a unidirectional relation between FDI and industrial productivity. The findings suggest that South Asian economies should invest in and encourage the transition to RE transition and modernization and remove strict regulations from the agriculture and industrial sectors.